2015
DOI: 10.1016/j.chembiol.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Intestinal Cancer by Local, Topical Application of a Quenched Fluorescence Probe for Cysteine Cathepsins

Abstract: SUMMARY Early detection of colonic polyps can prevent up to 90% of colorectal cancer deaths. Conventional colonoscopy readily detects the majority of pre-malignant lesions, which exhibit raised morphology. However, lesions that are flat and depressed are often undetected using this method. Therefore, there is a need for molecular-based contrast agents to improve detection rates over conventional colonoscopy. We evaluated a quenched fluorescent activity-based probe (qABP; BMV109) that targets multiple cysteine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 48 publications
(53 reference statements)
1
59
0
Order By: Relevance
“…We and others have previously demonstrated that small-molecule ABPs can be used to topically label active cathepsins in excised tissues (37,38). Two fresh human carotid endarterectomy specimens were split into sections to perform labeling using the optical probe BMV109 (Fig.…”
Section: Topical Application Of Activity-based Probe On Human Carotidmentioning
confidence: 99%
“…We and others have previously demonstrated that small-molecule ABPs can be used to topically label active cathepsins in excised tissues (37,38). Two fresh human carotid endarterectomy specimens were split into sections to perform labeling using the optical probe BMV109 (Fig.…”
Section: Topical Application Of Activity-based Probe On Human Carotidmentioning
confidence: 99%
“…The use of fluorescently labeled markers that target tumors allows clear detection of margins, making it possible to achieve complete tumor resection while preserving healthy surrounding structures and tissue. Investigators have recently developed molecular imaging probes to image disease-associated proteases [14][15][16][17][18] . In addition to being viable targets for the treatment of disease, proteases are also potential biomarkers for diagnostic purposes 19 .…”
Section: Existing Methods For Visualization Of Tumor Marginsmentioning
confidence: 99%
“…BMV109 contains a Cy5 fluorophore, a sulfo-QSY21 quencher and a phenoxymethyl ketone electrophile that labels cysteine cathepsins B, S, L and X 17,18 (Fig. 1a).…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations